EFFICACY OF 17-Î±-HYDROXY-PROGESTRONE IN PREVENTION OF PRETERM LABOR IN HIGH RISK PREGNANT WOMEN - Shadab, Wajiha; Riaz, Shazia; Aftab, Farzana; Shah, Faizan Hassan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Preterm delivery (before 37 completed weeks of gestation) is a major determinant of infant mortality. The objective of study was to determine the efficacy of 17-alpha hydroxy-progesterone in preventing delivery before 37 weeks of gestation in high risk women. Methods: This study, a randomized controlled trial was conducted in Obstetrics OPD, observing all scientific and ethical protocols. The women with less than 20 weeks gestation and with a past history of preterm delivery were included. A total of 132 women fulfilled the study requirements. Two groups made were as follows: Group A (Treatment group received intramuscular 17-alpha hydroxy-progesterone) and Group B served as control (The control group revived intramuscular Neurobion). A total of 66 women were assigned to each group. The data was recorded on a specially designed proforma for statistical analysis and comparison following the standard procedure. Results: The criterion was strictly observed. The results showed a statistically significant (p<0.01) difference between group A as compared to group B. Conclusion: 17-Î±-Hydroxyprogesterone was found to be an effective drug in preventing delivery before 37 weeks in women at risk. Keywords: 17-Alpha-hydroxyprogesterone; Preterm labour; High risk pregnancy